TSH-Secreting Pituitary Macroadenoma in a Girl with Lingual Thyroid - S. Wacharasindhu; S. Shuangshoti; S. Sunthornyothin (Case Reports in Endocrinology)
Patients with long-standing hypothyroid are, in some cases, reported to develop pituitary gland hyperplasia due to loss of feedback inhibition of thyroxine in hypothalamus—the condition of which typically regresses after thyroxine replacement. Herein, a 15-year-old girl—with long-standing untreated lingual hypothyroid—presents with a pathologically proven TSH pituitary macroadenoma and bilateral large ovarian cysts. Although MR imaging may differentiate between hyperplasia and macroadenoma of the pituitary gland, pathological examination is still a cornerstone to correct diagnosis.